A Low Cost Automated Weather Station for Real Time Local Measurements - Abdul-Niby, M.; Farhat, M.; Abdullah, M.; Nazzal, A. (Engineering, Technology & Applied Science Research, 2017)
In this paper, we present an automated weather station for real time and local measurements, based on an embedded system that continuously measures several weather factors such as temperature, humidity, barometric pressure, wind speed, wind direction, and rainfall. This weather station consists of two parts which are located indoor and outdoor and connected together wirelessly. The outdoor weather station measures the current temperature, humidity, barometric pressure, wind speed, wind direction and recent rain amount. The indoor station displays the outdoor reading as well as the temperature and humidity for the room it is located in, on a graphic liquid crystal display. In addition, this weather information can be accessed from any place through an iOS and Android application called Blynk.